Educación para la sostenibilidad turística y la conciencia ambiental en los estudiantes de la carrera de turismo de la Universidad Técnica de Babahoyo en el año 2024-2025 - Suarez Bajaña, Alis Samanta (2025)
The curricular integration project has the purpose of analyzing education and tourism sustainability to promote environmental awareness in students of the tourism major at the UTB (Technical University of Babahoyo). This purpose was complemented with specific objectives that include identifying the environmental knowledge of students, evaluating their waste management practices and proposing strategies that encourage their participation in environmental projects and community activities. A descriptive methodology was carried out with a mixed approach that allows collecting both quantitative and qualitative data to evaluate the knowledge, practices and behavior of students that are related to sustainability. Exploratory and explanatory research is used to gain a precise understanding of the diverse perspectives of students and teachers specialized in sustainability. The information collected in the research techniques applied to students and teachers allows us to evaluate the level of knowledge about sustainability that tourism students have, what waste management practices they carry out and what strategies teachers implement to promote environmental awareness in their students. Various challenges are identified to carry out a sustainable tourism system and improvements in academic training are proposed, relating them to the area of sustainability.